Changes in Sleep Quality Following Treatment for Chronic Rhinosinusitis: A Systematic Review and Meta-Analysis. Issue 3 (May 2022) - Fried, Jacob; Yuen, Erick; Gudis, David A.; Schlosser, Rodney J.; Nguyen, Shaun A.; Rowan, Nicholas R.
Background: Chronic rhinosinusitis (CRS) presents with broad and systemic manifestations, including impaired sleep; however, the impact of CRS treatments upon sleep is unknown. Objective: To establish the effect of medical or surgical CRS treatment on subjective and objective sleep metrics for patients not previously diagnosed with sleep apnea. Methods: Review of PubMed, Scopus, Web of Science, and the Cochrane Library was performed from the databases' date of inception through August 13, 2020, for studies evaluating the effect of CRS treatment on sleep quality. All studies reporting on subjective and objective sleep parameters for patients with CRS, with completed pre- and posttreatment data were included. Studies composed of patients with diagnosed sleep apnea were excluded. Results: Sixteen unique studies reporting data on a total of 1770 patients (mean age, 50.6 ± 15.6 (n = 1675) years) following treatment for CRS were included. Patient-reported outcome measures, Epworth Sleepiness Scale, Pittsburgh Sleep Quality Index, and Fatigue Severity Scale, demonstrated mean posttreatment differences of −2.8 (95% CI: −4.9 to −0.7), −2.4 (95% CI: −3.7 to −1.2), and −1.2 (95% CI: −1.6 to −0.7), respectively. The SNOT-22 and its sleep domain demonstrated a mean posttreatment difference of −23.5 (95% CI: −31.7 to −15.3) and −5.4 (95% CI: −6.8 to −4.0), respectively. EpSS, FSS and SNOT-22 exceeded their respective reported MCID values. Objective findings did not significantly change with treatment; mean difference: AHI: 0.7 (95% CI: −1.5 to 2.9), oxygen nadir: 0.3 (95% CI: −0.4 to 0.9). Conclusions: Treatment of CRS may lead to clinically meaningful reduction in disease burden and improvements in both overall sleep quality and patient-reported fatigue. Despite clinically meaningful quality of life improvements, objective sleep parameters did not demonstrate corresponding posttreatment improvements.